PROTECT MARINE ENVIRONMENTAL IN THE STRAITS OF MALACCA: COASTAL COUNTRIES COOPERATION - Feriana Kushindarti (2013)
As one of important marine crossroad in the world, the Straits of Malacca bordered by Malaysia, Indonesia and Singapore face some environmental problem due to shipping activities and industries around the Straits. Shipping activities and industries in the Straits contribute to the increasing of marine pollution. The increasing of marine pollution will impact to marine living resources such as coral reef development and fishing resources, mangrove ecosystem and coastal inhabitant. As coastal coun